A47. Community Acquired Pneumonia and Healthcare Associated Pneumonia 2009
DOI: 10.1164/ajrccm-conference.2009.179.1_meetingabstracts.a1729
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Culture-Negative and Culture-Positive Health Care-Associated Pneumonia.

Abstract: Background:Health care−associated pneumonia (HCAP) has been associated with pathogens that are often multi−drug resistant and practice guidelines suggest initial treatment should be similar to hospital−acquired and ventilator−associated pneumonia. Objective: Describe the initial antibiotic treatment regimens, severity of illness, and in−hospital mortality among culture−negative (CN) and culture−positive (CP) patients with HCAP. Methods: A retrospective cohort study including 439 CN and 161 CP patients with HCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Our data agree with previous reports suggesting that the current HCAP definition has poor sensitivity for patients most likely to harbor a resistant pathogen versus those who do not. 7,18,21 High rates of clinical and microbiological success were achieved throughout the study period, despite a reduction in FQ days and frequency of double coverage in the postintervention period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our data agree with previous reports suggesting that the current HCAP definition has poor sensitivity for patients most likely to harbor a resistant pathogen versus those who do not. 7,18,21 High rates of clinical and microbiological success were achieved throughout the study period, despite a reduction in FQ days and frequency of double coverage in the postintervention period.…”
Section: Discussionmentioning
confidence: 97%
“…Patients were included only if the following criteria were met ( a ) radiographic findings consistent with pneumonia plus 2 or more of the following signs of infection: temperature >100.4°F or <96.8°F, white blood cells >12 or <4 ×1000/µL, presence of cough or shortness of breath, and new or increased O 2 requirement; ( b ) presence of at least 1 guideline-concordant HCAP risk factor; ( c ) treated with ≥1 anti- Pseudomonas β-lactam initiated within 24 hours of admission. 18 Anti- Pseudomonas β-lactams were defined as piperacillin-tazobactam, cefepime, ceftazidime, meropenem, imipenem, doripenem, or aztreonam.…”
Section: Methodsmentioning
confidence: 99%
“…Despite one previous HCAP study with culture negative data using the criteria of MRSA and single agent P aeruginosa coverage as their appropriate regimen, it was felt that double coverage was more in line with the guideline recommendations and consistent with multiple other HCAP studies analyzing empiric therapy. 1,5,13,14 In addition, it was decided that including culture negative data increased external validity as the majority of patients with HCAP do not have lower respiratory cultures drawn in the ED. 15…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lower respiratory and intra-abdominal infections were predominant in our culture-negative group, which suggests the site of infection may be associated with CNSS. Previous retrospective studies found that culture-positive patients with lung and intra-abdominal infections were associated with poor outcomes [23,24]. The authors thought that culture-negativity might imply susceptibility to the initial antibiotic regimens prescribed, leading to a lesser severity of illness.…”
Section: Discussionmentioning
confidence: 99%